Minimal Units of Consciousness and Possible Evolution of Intelligence - Funk, Richard H. W. (European Journal of Applied Sciences, 2024)
The present review attempts to find out what are basic elements of consciousness - that is, what are the characteristics of purposeful perceptions and "reactive" actions observed in living beings. The difference between consciousness and intelligence is also dealt with in this respect. These considerations are based on previous work on feedback loops in "active" matter leading to "living matter". To follow this line, we briefly look at the development of information processing and the formation of neural networks in evolution, culminating in the formation of the human brain. As a synthesis, we deal with current hypotheses of biophysical processes that take place in the human brain in connection with consciousness and intelligence. Furthermore, it discusses basic principles of information processing in artificial intelligence and the difference between human consciousness and intelligence compared to AI. In doing so, we touch on philosophical questions such as the relationship to "minimal physicalism", which is related to teleonomy as a "weak form" of "panpsychism". Thus, the present review can also add some aspects to a lively discussion that has recently erupted on animal consciousness, culminating in the "New York Declaration on Animal Consciousness."